Carrier cascade : enabling high performance perovskite light-emitting diodes (PeLEDs) - Kulkarni, Sneha Avinash (2020)
In recent years, hybrid lead-halide perovskites have emerged as promising solution-processed semiconductors for thin-film optoelectronics with a growing focus on light-emitting diode applications. Perovskites exhibit remarkable flexibilities in structure and composition tuning and possess excellent intrinsic properties such as band gap tunability over a visible range, high colour purity emission, high photoluminescence quantum yield (PLQY) and high exciton binding energies. Recently, perovskite-based light-emitting diodes (PeLEDs) have exhibited external quantum efficiency of 14.36% and revealed the potential for further improvement. High PLQY is a key requirement for better PeLED performance. This can be realised by controlling the grain-size of the perovskite films with optimum active layer thickness and utilising reduced-dimensionality perovskite emitters to spatially confine charge carriers for enhanced radiative recombination. In this short review, we discuss the critical parameters required for efficient PeLEDs, the recent progress mainly highlighting the energy transfer mechanism within Ruddlesden Popper structures and graded size nanoparticle films. We also outline the recommendations and strategies for further improvement.